BUDAYA JALANAN DALAM KOMUNITAS VESPA JALANAN: KAJIAN ETNOGRAFI TENTANG IDENTITAS, EKSPRESI DIRI, KEBEBASAN, DAN SOLIDARITAS - Khairindana Putri; Maulid Hariri Gani; Gusneli (STKIP Subang, 2026)
The street culture within the Vespa street community is reflected in the use of vintage Vespas, which function not only as a means of transportation but also as symbols of identity, self-expression, freedom, and solidarity among members. Field observations revealed various types of Vespas, ranging from those that maintain their original classic character to modified versions such as the rat look style, featuring rusty bodywork, high handlebars, and sidecars made from recycled materials. Community gatherings commonly take place in open spaces, where members relax, discuss vehicle conditions, and perform minor repairs together. Interactions among members are informal and friendly, characterized by casual conversations, the exchange of travel experiences, and mutual assistance when mechanical problems occur on the road. This togetherness demonstrates that vintage Vespas serve as a medium for building close social relationships and strengthening collective identity within street culture.